1999
DOI: 10.1097/00125817-199911000-00001
|View full text |Cite
|
Sign up to set email alerts
|

Malformations reported in chorionic villus sampling exposed children: A review and analytic synthesis of the literature

Abstract: CVS-exposed children have an increased frequency of intestinal atresia, gastroschisis, and clubfoot compared with the nonexposed population. The fact that an increased frequency of other defects attributed to vascular disruption was not found may be due to under-ascertainment, misclassification, or "lumping" of the defects identified in previous studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 31 publications
(12 citation statements)
references
References 40 publications
(1 reference statement)
0
12
0
Order By: Relevance
“…Clinical observations offer further support on a case-by-case basis. Cases of monozygous twinning, tubal pregnancies, bicornate uterus, misoprostol, or chorionic villous sampling associated with the amniotic band phenotype (McGuirk and others, 2001; Stoler and others, 1999; Van Allen, 1981) offer compelling evidence for a vascular disruption etiology, but these published cases appear to represent a very small fraction of most amniotic band or limb reduction cases.…”
Section: Discussionmentioning
confidence: 99%
“…Clinical observations offer further support on a case-by-case basis. Cases of monozygous twinning, tubal pregnancies, bicornate uterus, misoprostol, or chorionic villous sampling associated with the amniotic band phenotype (McGuirk and others, 2001; Stoler and others, 1999; Van Allen, 1981) offer compelling evidence for a vascular disruption etiology, but these published cases appear to represent a very small fraction of most amniotic band or limb reduction cases.…”
Section: Discussionmentioning
confidence: 99%
“…Additional analyses of the frequency of common malformations in children exposed to CVS 15 have shown an increased frequency of several other abnormalities, such as clubfoot and bowel atresia. Los et al 16 noted that these features have in common the presence of end arteries, which is the basis of abnormalities caused by poor perfusion of the brain stem, tongue, spinal cord, intestine, fingers, and toes.…”
Section: Other Associated Deformitiesmentioning
confidence: 99%
“…However, structural abnormalities of the central nervous system were not observed in those cases who had CNS imaging. Among these cases, where primarily the legs were involved, the ATP was most likely to occur between 8 and 9 embryonic weeks (10-11 gestational weeks) consistent with the concern that early amniocentesis is associated with an increased risk for arthrogryposis and clubfoot [Stoler et al, 1999].…”
Section: Discussionmentioning
confidence: 62%
“…Early amniocentesis and early CVS studies showed an increase in limb anomalies together with contractures, including clubfeet and arthrogryposis and these reported changes were compatible with vascular compromise [Singh et al, 1974;Cheng et al, 1991;Brambati et al, 1992;Froster and Baird, 1992;Halliday et al, 1992;Hanson et al, 1992;Greenough and Nicolaides, 1997;Stranc et al, 1997;Sundberg et al, 1997;Babay et al, 1998;Boyd et al, 1998;Stoler et al, 1999]. Maternal cocaine use during pregnancy, which also alters vascular supply, has been associated with congenital contractures suggesting that vascular compromise may play a role in this type of limb anomaly [Acker et al, 1983;Chavez et al, 1989;Lipson et al, 1989;Handler et al, 1991].…”
Section: Discussionmentioning
confidence: 99%